Impact of Integrated Care Management on Clinical Outcomes in Atrial Fibrillation Patients: A Report From the FANTASIIA Registry - Esteve-Pastor, María Asunción; Ruiz-Ortiz, Martín; Muñiz, Javier; Roldán-Rabadán, Inmaculada; Otero, Déborah; Cequier, Ángel; Bertomeu-Martínez, Vicente; Badimón, Lina; Anguita, Manuel; Lip, Gregory Y. H.; Marín, Francisco (Frontiers in Cardiovascular Medicine, 2022)
Background An integrated and holistic approach is increasingly advocated in patients with atrial fibrillation (AF), based on the “Atrial fibrillation Better Care (ABC) pathway: A, Avoid stroke with anticoagulation; B, better symptom management; C, cardiovascular and comorbidity risk management.” The aim of this study was to examine the prevalence of adherence to each component of the ABC pathway and to analyze its impact on long-term prognosis in the “real-world” cohort of AF patients from the FANTASIIA registry. Methods This prospective study included consecutive AF outpatients anticoagulated with direct oral anticoagulants (DOAC) or vitamin K antagonists (VKA) from June 2013 to October 2014. From the ABC pathway, adherence to the “A criterion” was defined by a time in the therapeutic range (TTR) ≥ 70% or correct dose with DOAC; “B criterion” adherence was defined by a European Heart Rhythm Association (EHRA) Symptom Scale I-II; and “C criterion” adherence was defined as optimized risk factors and comorbidity management. Baseline features and embolic events, severe bleeding, and all-cause and cardiovascular mortality rates up to 3 years of follow-up were analyzed, and a Cox multivariate analysis was performed to investigate the role of each component of the ABC pathway in predicting major events. Results A total of 1,955 AF patients (age: 74.4 ± 9.4 years; 43.2% female patients) were included in this study: adherence to A criterion was observed in 920 (47.1%) patients; adherence to B criterion was observed in 1,791 (91.6%) patients; and adherence to C criterion was observed in 682 (34.8%) patients. Only 394 (20.2%) of the whole population had good control of AF according to the ABC pathway. After a median follow-up of 1,078 days (IQR: 766–1,113), adherence to A criterion was independently associated with reduced cardiovascular mortality [HR: 0.67, 95%CI (0.45–0.99); p = 0.048] compared with non-adherence. Adherence to the B criterion was independently associated with reduced stroke [HR: 0.28, 95%CI (0.14–0.59); p < 0.001], all-cause mortality [HR: 0.49, 95%CI (0.35–0.69); p < 0.001], cardiovascular mortality [HR: 0.39, 95%CI (0.25–0.62); p < 0.001], and major adverse cardiovascular events (MACE) [HR: 0.41, 95%CI (0.28–0.62); p < 0.001] compared with non-adherence. AF patients with C criterion adherence had a significantly lower risk of myocardial infarction [HR: 0.31, 95%CI (0.15–0.66); p < 0.001]. Fully adherent ABC patients had a significant reduction in MACE [HR: 0.64, 95%CI (0.42–0.99); p = 0.042]. Conclusion In real-world anticoagulated AF patients from FANTASIIA registry, we observed a lack of adherence to integrated care management of AF following the ABC pathway. AF managed according to the ABC pathway was associated with a significant reduction in adverse outcomes during long follow-up, suggesting the benefit of a holistic and integrated approach to AF management.